Novel pilot protection scheme for line‐commutated converter high voltage direct current transmission lines based on behaviour of characteristic harmonic impedances. Issue 2 (4th December 2020) - Dehghan Marvasti, Farzad; Mirzaei, Ahmad; Hamedani Golshan, Mohamad Esmail
Abstract: Transient behaviour of high‐voltage direct current transmission lines under direct current faults can be easily affected by many factors, namely, fault location, fault resistance and transmission line length. In order to design a suitable protective scheme, the impact of these factors should be thoroughly investigated. An impedance‐based analysis is more suitable in evaluating high‐voltage direct current system behaviour during direct current line faults, and consequently, in comparison to similar harmonic current or voltage‐based schemes, a characteristic harmonic impedance‐based protection is more capable in fault detection. Therefore, this paper presents a novel pilot protection method for line‐commutated converter based high‐voltage direct current transmission lines, which relies on continuous monitoring of characteristic harmonic impedances. The proposed method can accurately calculate location of faults along the line, and estimate additional valuable information, such as fault resistance. The validity of the proposed method is evaluated by a wide range of fault scenarios using the CIGRE high‐voltage direct current benchmark model, simulated in PSCAD/EMTDC and codes written in MATLAB software environments. It will be shown that the proposed protection method sounds promising, and can serve as an excellent backup option in the case of primary protection malfunction.